Plankton Assessment in Kuwait Bay - Al-Awadhi, Jasem; Al-Awadhi, Qaderyya; Moustafa, Hesham (IJRDO-Journal of Applied Science, 2019)
Assessment of phytoplankton and zooplankton biomass in Kuwait Bay was performed during December 2017 and April 2018, in relation to different seawater parameters along five locations across the bay. The results during winter 2017, showed that temperature, water clarity and silicates were highly correlated with phytoplankton abundance, while, salinity and TSS, were positively correlated with zooplankton abundance. On the other hand, during spring 2018, dissolved oxygen and water clarity were highly correlated with phytoplankton biomass, while silicates and temperature were positively correlated with zooplankton abundance.